Delayed perturbation of Mittag-Leffler functions and their applications to fractional linear delay differential equations - Mahmudov, Nazim I. (Wiley, 2019)
In this paper, we propose a delayed perturbation of Mittag-Leffler type matrix function, which is an extension of the classical Mittag-Leffler type matrix function and delayed Mittag-Leffler type matrix function. With the help of the delayed perturbation of Mittag-Leffler type matrix function, we give an explicit formula of solutions to linear nonhomogeneous fractional delay differential equations.
Keywords: delayed perturbation; fractional linear systems; Mittag-Leffler type matrix function